Ambient bloom: New business, content, design and models to increase the semantic ambient media experience - Pogorelc, B.; Lugmayr, Artur; Stockleben, B.; Vatavu, R.; Tahmasebi, N.; Serral, E.; Stojmenova, E.; Imperl, B.; Risse, T.; Zenz, G.; Gams, M. (2013)
Semantic ambient media are the novel trend in the world of media reaching from the pioneering subareas such as ambient advertising to the new and emerging subareas such as ambient assisted living. They will likely shape the upcoming years in terms of modeling smart environments and also media consumption and interaction. This work analyzes semantic ambient media by considering business models, content and media, interaction design and consumer experience, and methods and techniques that are important to create this new form of media. Discussion is led using the state-of-the-art event of the semantic ambient media, which is the annual international workshop on Semantic Ambient Media Experience (SAME). The study also creates a vision for how ambient media will evolve and how they will look like in the future decade. © 2012 Springer Science+Business Media, LLC.